IMPLEMENTASI PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR : KAJIAN LITERATUR - Rahma Fadhilah; Elfia Sukma; Inggria Kharisma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the RME approach to mathematics learning in elementary schools through a literature review. The method used is a literature review that analyses various national and international journal articles from databases such as Google Scholar and ScienceDirect, followed by content analysis. The results of the study indicate that teachers are required to use learning approaches that can improve mathematics learning in students. One approach that allows students to improve their mathematical abilities is Realistic Mathematics Education (RME). This approach helps students understand mathematical concepts through real-world problems, as many students still have difficulty grasping problem-solving in mathematics. These students will generally be proficient in calculations, but when faced with story problems, they will have difficulty understanding the context. This is caused by a reliance on formulas without a deep understanding of the basic principles of the formula. In this condition, it can be a major cause of student failure because the learning method is not effective in building a deep understanding of mathematical concepts. Therefore, the RME approach is needed in mathematics learning in elementary schools.